Spoken Latin: Learning, Teaching, Lecturing and Research - A. Gratius Avitus (The Journal of Classics Teaching, 2018)
My experiences both as a learner and as a teacher of Latin have led me to the conviction that speaking Latin advances a more nuanced understanding of the language, and leads to an enhanced level of reading fluency and greater ease in engaging closely with the text. Even after having studied the language to any degree of competence in a passive capacity, bringing it into active use does not come without some investment of time and effort. With the intention of facilitating access to the benefits of speaking Latin fluently, I have set out some recommendations for those who would like to explore this approach, and put together an overview of its recent spread in formal teaching, and in research, around the UK and Europe. It is my hope that in drawing attention to the rapidly increasing number of initiatives, this article will promote cross-fertilisation of ideas between the disparate influencers in the field of Latin pedagogy.